TRANSFORMATION PROCESSES OF MODERN LABOUR MARKET IN UKRAINE - Krikun, Olga (Social Economics, 2016)
A study of the modern labor market in Ukraine and identified the main problems of formation and regulation of the labor market in the face of constant reforms and changes. Designated stages of transformation processes in the labor market have established the labor that is in demand in the professional field of activity and make recommendations that support the nature of the labor market at the stage of reform and permanent changes.